(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This study examined the relationship between team work and service quality delivery in the medical sector at the University of Port Harcourt Teaching Hospital (UPTH). Specifically, the study tested how trust, cohesiveness, and spirit de corps, relate to service quality delivery in the medical sector. This descriptive survey study obtained primary data from 80 service personnel at the teaching hospital with a standardised questionnaire using a 4-point Likert scale. Cronbach’s Alpha was used to evaluate the tool’s dependability, and a threshold of 0.7 was determined to ensure internal consistency. To analyse the data, the Pearson Product-Moment Correlation (PPMC) coefficient was used; SPSS version 22 was deployed to enable the inferential statistics. The findings indicate a positive and significant relationship between the three aspects of trust, cohesiveness, and spirit de corps and service quality delivery. This study concludes that structured interventions that develop and sustain effective teamwork dynamics to achieve sustainable service quality improvements is needed in organisations. It was recommended that UPTH should regularly organize team-building activities and workshops to enhance trust, cohesion, and spirit de corps among employees among others.